APPLICATION OF TESTING TECHNOLOGY IN PROGRAM TRAINING - A. E. Makarenko (Вестник университета, 2021)
The purpose of the paper is to improve the methods of using test technologies in the educational process and to develop an optimal schedule for conducting tests in higher education when teaching programming languages. The article considers the advantages and disadvantages of test technologies. The author investigates the effectiveness of one-time and step-by-step testing and studies the role of testing at different stages of the educational process. In the course of the study, the author used written and computer forms of testing. The paper shows that step-by-step testing is more effective than one-time testing. The article identifies the expediency of testing that precedes the implementation of practical work. The results of the study allow us to develop an optimal schedule for conducting tests, which contributes to improving the quality of learning material and increasing students’ motivation.